An application of expert system in prequalifying contractors using -C- / Mohd Arif Ibrahim - Ibrahim, Mohd Arif (1991)
The purpose of this project is to generate a computer program which apply *Expert System' to automate the prequalifying process of contractors in civil works. Expert system can be defined as a storage of expertise or knowledge base into a database form in order to come to a specific decision. An expert system is actually an artificial intelligence system to solve problems in a particular domain which contain a manageable amount of information. In the case of this study, the domain used is a set of information and rules aquired from people who are expert in contractor's prequalifying process. This program consist of 4 examples of database to prequalify a contractor for specific civil work contracts or in other word to determine the contractor's capability to undertake specific works for which bids are to invited. His concept of evaluation used here is based on the scoring system, that is the establishment of groups of evaluation factors and assignment of a minimum score to be reached for each group. On the application side, this computer program could enormously reduce the decision time taken for evaluating each contractor while maintaining high accuracy of each decision made. It also eliminates the human factor such as bias during the decision making.